2020
DOI: 10.1007/s11524-020-00428-8
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Structural and Neighborhood Predictors of Incident Criminal Justice Involvement in a Population-Based Cohort of Young Black MSM and Transgender Women

Abstract: Black men who have sex with men (MSM) and transgender women are disproportionately affected by criminal justice involvement (CJI) and HIV. This study recruited 618 young Black MSM and transgender women in Chicago, IL, using respondent-driven sampling between 2013 and 2014. Random effects logistic regression evaluated predictors of incident CJI over 18 months of follow-up. Controlling for respondent age, gender and sexual identity, spirituality (aOR 0.56, 95% CI 0.33-0.96), and presence of a mother figure (aOR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 58 publications
(76 reference statements)
2
6
1
Order By: Relevance
“…Consistent with research in this and a similar Los Angeles study population, there were no positive associations between marijuana use and incarceration, risky behaviors, or negative health outcomes [ 40 ]. Findings are inconsistent with a similar analysis that our group conducted in a Chicago cohort of young Black transgender women and MSM, where we found increased odds of incident incarceration in participants who used marijuana only compared with participants who did not use substances [ 41 ]. Prior to January 2020, even medical marijuana was illegal in Illinois.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Consistent with research in this and a similar Los Angeles study population, there were no positive associations between marijuana use and incarceration, risky behaviors, or negative health outcomes [ 40 ]. Findings are inconsistent with a similar analysis that our group conducted in a Chicago cohort of young Black transgender women and MSM, where we found increased odds of incident incarceration in participants who used marijuana only compared with participants who did not use substances [ 41 ]. Prior to January 2020, even medical marijuana was illegal in Illinois.…”
Section: Discussioncontrasting
confidence: 99%
“…Consistent with prior research on the general U.S. population, we found that incarceration history was positively associated with public health insurance status, Black race/ethnicity, low income (with and without recent homelessness), recent stimulant use, and depression symptoms for Black and Latino MSM in Los Angeles [ 24 , 26 , 36 , 41 , 43 ]. Over 90% of the sample was low-income or had public or no health insurance, over 55% used stimulants, and 42% had symptoms consistent with depression.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Tieu et al [5] offer potential pathways by which neighborhood-and network-level factors affect the HIV care continuum for Black MSM while Cassels et al [6] identified place-related patterns that influenced HIV vulnerability and access to health care among substance-using Black MSM in Los Angeles. Hotton et al [7] investigated neighborhood-level and socio-structural predictors of criminal justice involvement among MSM in Chicago, which is a particularly salient topic given how the over-policing and criminalization of Black communities hasled to large proportions of Black men being exposed to the criminal justice system. Yang et al [8] also tackle this phenomenon of criminal justice involvement among African American MSM in Baltimore, its association with transactional sex, and its implications for their re-integration into communities.…”
mentioning
confidence: 99%
“…Using data from the largest domestic prospective cohort study of Black MSM (HPTN 061)-drawn from six cities (i.e., Atlanta, Boston, Los Angeles, New York, San Francisco, Washington DC)-Okafaor et al [13] found that most participants living with HIV communicated their status to their last male sex partner and that disclosure was associated with lower odds of condomless receptive anal intercourse with an HIV serodiscordant or HIV status unknown partner. The positive role of social support on HIV prevention and treatment engagement is highlighted across four articles-including the value of spiritual/religious support [14], support from parental figures [7,14,15], peer support [14][15][16], and the salience of transgender women in the social support networks of Black MSM [15,16]. Finally, Robbins et al [17] identify trends among adolescent sexual minority men between alcohol/substance use and behaviors that may increase their likelihood of exposure to HIV while Gordían-Arroyo et al [18] round out the issue identifying the opportunity for PrEP implementation with their evidence of high awareness and willingness to use PrEP among a mostly Black and multi-racial sample of adolescent sexual minority men drawn from across the USA.…”
mentioning
confidence: 99%